PROMOTING EFFECTIVE COMPLIANCE IN CIVIL SERVICE DISPUTE JUDGMENTS: A Cross-Jurisdictional Study - Nasrullah Nasrullah; I Gusti Ayu Ketut Rachmi; Lego Karjoko; King Faisal Sulaiman; Nurul Satria Abdi; Muhammad Arya Ansar (Al-Risalah, 2026)
Despite the final and binding nature of Administrative Court (PTUN) decisions in Indonesia, their enforcement remains critically low, particularly in civil service disputes. Data indicate that only about 2% of 16,484 PTUN rulings with permanent legal force were voluntarily implemented by administrative officials between 2012 and May 2025. This research employed a normative legal method combined with statutory, case, and comparative approaches to examine the systemic barriers to execution. The findings demonstrated that the ineffectiveness of PTUN decision enforcement arose, in abstracto, from regulatory ambiguity regarding execution mechanisms and institutional authority, and, in concreto, from a low-compliance culture among administrative officials. In contrast, Thailand recorded an execution rate of approximately 92% in civil service disputes, supported by clear coercive powers and contempt-of-court sanctions, while Germany achieved high compliance through integrated legal frameworks and independent supervisory institutions. This study has advocated reforming Indonesia’s PTUN system by granting the Head of the Administrative Court supervisory and enforcement powers and introducing a civil contempt mechanism to enhance compliance, bolster judicial efficacy, and advance administrative justice in judgments on civil service disputes.